Quadruplex-forming sequences occupy discrete regions inside plant LTR retrotransposons - Lexa, Matej; Kejnovský, Eduard; Steflová, Pavlína; Konvalinová, Helena; Vorlícková, Michaela; Vyskot, Boris (Nucleic acids research, 2014)
Retrotransposons with long terminal repeats (LTR) form a significant proportion of eukaryotic genomes, especially in plants. They have gag and pol genes and several regulatory regions necessary for transcription and reverse transcription. We searched for potential quadruplex-forming sequences (PQSs) and potential triplex-forming sequences (PTSs) in 18 377 full-length LTR retrotransposons collected from 21 plant species. We found that PQSs were often located in LTRs, both upstream and downstream of promoters from which the whole retrotransposon is transcribed. Upstream-located guanine PQSs were dominant in the minus DNA strand, whereas downstream-located guanine PQSs prevailed in the plus strand, indicating their role both at transcriptional and post-transcriptional levels. Our circular dichroism spectroscopy measurements confirmed that these PQSs readily adopted guanine quadruplex structures-some of them were paralell-stranded, while others were anti-parallel-stranded. The PQS often formed doublets at a mutual distance of up to 400 bp. PTSs were most abundant in 3'UTR (but were also present in 5'UTR). We discuss the potential role of quadruplexes and triplexes as the regulators of various processes participating in LTR retrotransposon life cycle and as potential recombination sites during post-insertional retrotransposon-based genome rearrangements.
Keywords: G-Quadruplexes; Genome, Plant; sekvenční analýza DNA; genom rostlinný; G-kvadruplexy; Retroelements; koncové repetice; retroelementy; DNA rostlinná; Sequence Analysis, DNA; DNA, Plant; Terminal Repeat Sequences